Penapisan Fitokimia dan Uji Hayati secara BSLT dari Daun, Buah dan Biji Phaleria macrocarpa - Suci Eka Lestari; Ratna Djamil (JURNAL ILMU KEFARMASIAN INDONESIA, 2005)
Mahkota Dewa (Phaleria macrocarpa [Scheff] Boerl), is Indonesian herb that famous for its medicinal activity. The chemical constituens of the leaves, fruits and seeds have been examined, and BSLT (brine shrimp lethality test) have been carried out. On phytochemical screening, the leaves showed the existence of: volatile oil, sterol, triterpene, higher fatty acid, alkaloid, flavon aglycon, coumarine, tannin, steroid glycoside, flavonoid, polyuronide and triterpene, the fruits contain: volatile oil, sterol, triterpene, higher fatty acid, alkaloid, flavon aglycon, coumarine, tannin, reducing compound, steroid glycoside, flavonoside, polyuronide and saponine; while the seeds contain: steroid, triterpene, higher fatty acid, alkaloid, flavon aglycon, coumarine, tannin, reducing compound, steroid glycoside and flavonoid. Brine shrimp lethality test showed that the LCs of the n-hexane fraction of the leaves, fruits and seeds are 2.34 ppm, 32.62 ppm and 4.33 10-28 ppm respectively; the aethyl acetate fraction of the leaves, fruits and seeds are 10.55 ppm, 29,12 ppm and 4.71 ppm respectively; while the methanol fraction of the leaves, fruits and seeds are 1.46.10-5ppm, 39.32 ppm, and 53.31 ppm respectively. From this study it may be concluded that the n-hexane and aethyl acetate fraction of the seeds have the most active compounds, while the leaves have the most active compounds in the ethyl acetate fraction.